Best Answer

There are numerous solutions to the formula A + BA + C = A + BC, some of them are:

* (0,1,1) * (5,2,10) * (4,5,5) * (7,8,8) * (3,4,4) * (6,3,9)

User Avatar

Wiki User

15y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: A plus BA plus C equals A plus BC?
Write your answer...
Still have questions?
magnify glass
Related questions

How is a plus b over a minus b equals c plus d over c minus d?

(a + b)/(a - b) = (c + d)/(c - d) cross multiply(a + b)(c - d) = (a - b)(c + d)ac - ad + bc - bd = ac + ad - bc - bd-ad + bc = -bc + ad-ad - ad = - bc - bc-2ad = -2bcad = bc that is the product of the means equals the product of the extremesa/b = b/c

5a plus d - bc equals a equals 5 b equals 7 c equals 2 d equals 4 what is the correct answer?


What is the simplified solution to BC plus 0 equals f?

f = B x C

If a plus b equals c and b plus c equals d and c plus d equals e and a equals 7 and e equals 5 what is a plus b plus c plus d plus e equal?

the answer is a

A plus b plus c whole square?

(a+b+c) 2=a2+ab+ac+ba+b2+bc+ca+cb+c2a2+b2+c2+2ab+2bc+2ca [ ANSWER!]

1 plus x equals b c plus x equals d d plus x equals 89 b plus x equals c d equals?

1+x=dd+x so dd=1 so d=1 1+x=89b+x so 89b=1 so b=1/89 bc+x=1+x so bc=1 so c=1/(1/89) = 89 so cd=89 (and x=88)

Which if the following is a factor b squared plus bc munus 2c squared equals?

(b + 2c)(b - c)

If we know that AB plus BC equals AC then what would be a conclusion?

You could conclude that B lies between A and C.

Rays BA and BC such that B is between A and C?

A Line Bisector

If a plus b plus c not equal to 0 then a divided by b plus c equals b divided by c plus a equals c divided by a plus b prove that a equals b equals c?

Because there is no way to define the divisors, the equations cannot be evaluated.

Use Boolean algebra to simplify the logic function and realize the given function and minimized function using discrete gates. f equals ab c plus abc plus ac plus bc plus abC.?

Do you mean F = abc + abc + ac + bc + abc' ? *x+x = x F = abc + ac + bc + abc' *Rearranging F = abc + abc' + ab + bc *Factoring out ab F = ab(c+c') + ab + bc *x+x' = 1 F = ab + ab + bc *x+x = x F = bc

If a plus a equals b and b plus c equals a and a-c equals b what is c?

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)